The Alice Springs Hospital Readmission Prevention Project (ASHRAPP): a randomised control trial - Gabrielle Diplock; James Ward; Simon Stewart; Paul Scuffham; Penny Stewart; Carole Reeve; Lea Davidson; Graeme Maguire (BMC, 2017)
Abstract Background Hospitals are frequently faced with high levels of emergency department presentations and demand for inpatient care. An important contributing factor is the subset of patients with complex chronic diseases who have frequent and preventable exacerbations of their chronic diseases. Evidence suggests that some of these hospital readmissions can be prevented with appropriate transitional care. Whilst there is a growing body of evidence for transitional care processes in urban, non-indigenous settings, there is a paucity of information regarding rural and remote settings and, specifically, the indigenous context. Methods This randomised control trial compares a tailored, multidimensional transitional care package to usual care. The objective is to evaluate the efficacy of the transitional care package for Indigenous and non-Indigenous Australian patients with chronic diseases at risk of recurrent readmission with the aim of reducing readmission rates and improving transition to primary care in a remote setting. Patients will be recruited from medical and surgical admissions to Alice Springs Hospital and will be followed for 12 months. The primary outcome measure will be number of admissions to hospital with secondary outcomes including number of emergency department presentations, number of ICU admissions, days alive and out of hospital, time to primary care review post discharge and cost-effectiveness. Discussion Successful transition from hospital to home is important for patients with complex chronic diseases. Evidence suggests that a coordinated transitional care plan can result in a reduction in length of hospital stay and readmission rates for adults with complex medical needs. This will be the first study to evaluate a tailored multidimensional transitional care intervention to prevent readmission in Indigenous and non-Indigenous Australian residents of remote Australia who are frequently admitted to hospital. If demonstrated to be effective it will have implications for the care and management of Indigenous Australians throughout regional and remote Australia and in other remote, culturally and linguistically diverse populations and settings. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12615000808549 - Retrospectively registered on 4/8/15.